Experiential Learning: Moving From Data Collection to Health Promotion in One Term. (September 2020) - Cunningham, Amy; Riley, Amy Henderson; Puskarz, Katherine; Frasso, Rosemary
Public health graduate students can benefit from exposure to both qualitative methods and health communication strategies early in their training. However, effective methods of integrating these constructs in an introductory course assignment have not been fully explored. This article describes a graduate public health assignment that engaged students in qualitative freelisting data collection and analysis to understand the health concerns of graduate students. Results of the freelisting exercise then informed the creation of infographics. Classroom sessions focused on instruction in freelisting data collection, data analysis, health communication principles, and infographic creation. A total of 73 MPH (Master of Public Health) students completed 355 freelisting interviews, examining the health priorities of graduate students. The most salient student priorities were sleep, exercise, eating, social/family time, balance, and mental health. Students worked in small groups to create infographics on one of the identified community priorities. Infographics were presented in class, posted in campus buildings, and shared through social media. The assignment offered students an experiential learning activity that integrated qualitative research and health communication strategies that provided a benefit to their community.